Values education, quality teaching, and service learning: the harmony of a new pedagogy? - Toomey, Ron; Lovat, Terry (Springer Publishing Company, 2009)
In a world increasingly wrestling with global issues like conflict resolution, human rights, sustainability, intercultural harmony, and the like, values education has gained renewed prominence. In Australia, China, including Hong Kong and Taiwan, Europe, including Russia, Ukraine and Iceland, South Korea, Singapore, Vietnam, Malaysia, and parts of Africa, values education is either a mandated part of the curriculum, with teachers in training being required to prepare for teaching it, or is at least a focused part of policy development. Typically, values education has been conceived of as a bolted-on component of the curriculum. This article presents a novel conception of values education, in which such content is not conceptualized as a subject or unit within the curriculum but rather in terms of a new pedagogy that affects the entire curriculum and the way it is taught. In this guise, values education has a greater capacity to produce the type of citizenry that can deal effectively with the major global issues of our day. Such a conception of values education arose from the authors' research experiences with the Australian government's recent values education initiatives, which are described in the article; these experiences were instrumental to the authors in the development of their novel conception of values education.